Adapting technology in Saudi libraries | تطويع التقنية في المكتبات السعودية - Al Salem | السالم, Salem bin mohammad | سالم بن محمد (King Fahad National Library | مكتبة الملك فهد الوطنية, 2024)
The text indicates that Saudi libraries began using technology since the 1960s, with the aim of improving their services, developing their systems, and expanding the number of beneficiaries. Libraries have succeeded in acquiring advanced devices and systems in the field of computer and communications technology, but they are still unable to fully benefit from the capabilities of these devices and systems. This is due to a number of factors, including: Differences in political, social, climatic and economic conditions between developed and developing countries. The information structure and equipment vary between the aforementioned countries. Libraries' dependence on foreign cadres, especially in selection, operation and maintenance processes. Relying on ready-made programs, without working to develop local programs that are relevant to the necessary needs. The text stresses the importance of developing a national strategic plan to adapt technology in Saudi libraries, so that the process is based on clear foundations that are far from individual judgments. The plan should also focus on developing qualified human resources and supporting scientific research in the field of information technology. | يشير النص إلى أن المكتبات السعودية بدأت في استخدام التقنية منذ الستينيات من القرن الماضي، وذلك بهدف تحسين خدماتها وتطوير نظمها وتوسيع رقعة المستفيدين. وقد نجحت المكتبات في اقتناء الأجهزة والنظم المتطورة في مجال تقنية الحاسوب والاتصالات، إلا أنها لا تزال عاجزة عن تحقيق الاستفادة الكاملة من إمكانات تلك الأجهزة والنظم. ويرجع ذلك إلى عدد من العوامل، منها: اختلاف الظروف السياسية والاجتماعية والمناخية والاقتصادية بين الدول المتقدمة والدول النامية. تفاوت بنية المعلومات وتجهيزاتها بين الدول المشار إليها. اعتماد المكتبات على الكوادر الأجنبية خصوصاً في عمليات الاختيار والتشغيل والصيانة. الاعتماد على البرامج الجاهزة، دونما العمل على تطوير برامج محلية لصيقة بالاحتياجات الضرورية. ويؤكد النص على أهمية وضع خطة إستراتيجية وطنية لتطويع التقنية في المكتبات السعودية، بحيث تقوم العملية على أسس واضحة بعيدة عن الاجتهادات الفردية. كما ينبغي أن تركز الخطة على تطوير العنصر البشري المؤهل، ودعم البحث العلمي في مجال تقنية المعلومات.